Abd al-Muttalib Daoud Mahdi Al-Husayni Al-Hilli and his role in the Literary and intellectual Renaissance (1865-1920). - Nadia Jasem Kadhim Ali / Hala Mahdi kayri Al-Dulaimi ((Humanities, social and applied sciences) Misan Journal of Academic Studies, 2022)
The study explained that Abd al-Muttalib Daoud al-Hilli was one of the distinguished Iraqi Personalities in the Context of Studying the History of modern and contemporary Iraq. Abd al-Muttalib was a famous jurist, writer, and poet, and one of the most famous figures of literature in Mesopotamia for nearly forty years. He was characterized by accuracy and intelligence. He was one of the most famous pioneers of the intellectual movement in the nineteenth and twentieth centuries. This was collected, explained, and published by the poetic bureaus, which were considered a forum for the creation of poetry and a platform for poets to reconcile, and models for scholars and writers of his time to emulate, and were considered sources from which researchers draw accurate information at present. DOI/10.54633/2333-021-042-002